Isolation of Phenolic Acid Compounds and Antioxidant Tests from Mindi Leaves (Melia azedarach L.) - Andriyani Budi Listyo; Dewi Kusrini; Enny Fachriyah (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2018)
Melia azedarach L plant categorized as traditional medicinal plant is normally used as a medicine for cough, skin diseases, drug for malaria, diabetes, colon cancer, jaundice, vaginal discharge, fever and scabies. Melia azedarach leaves contain steroid, terpenoid, alkaloid, tannin, saponin, phenolic and flavonoid compounds. The purpose of this study was isolation of phenolic acid compounds and antioxidant activity test from Melia azedarach L. Leaves. The method used to isolate phenolic acid using 3 ways that were alkaline hydrolysis (HB), acid hydrolysis (HA), and without hydrolysis (TH). The separation of phenolic acid which has Rf not the same as standard phenolic acid was undertaken by preparative TLC and characterized using UV-Vis spectrophotometer, FT-IR, and LC-MS. Moreover, antioxidant test of phenolic acid using DPPH method was also conducted. The results showed that isolation of Melia azedarach L. Leaves resulted in HB, HA and TH fractions with the weight of 1.05 grams, 1.26 grams and 1.38 grams, respectively. The identification of phenolic acid which has Rf the same as standard phenolic acids was ferulic acid. While result of phenolic acid (FA) isolates which has Rf not the same as phenolic acids standard was caffeic acid after the identifying using UV-Vis spectrophotometer, FTIR and LC-MS. Qualitative antioxidant activity test showed that FA isolate had IC50 of 168,650 ppm. This result indicated that FA isolate is potential as antioxidant compound.